2021
DOI: 10.7150/thno.55573
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3-mediated deacetylation of NLRC4 promotes inflammasome activation

Abstract: Salmonella typhimurium ( S. typhimurium ) infection of macrophage induces NLRC4 inflammasome-mediated production of the pro-inflammatory cytokines IL-1β. Post-translational modifications on NLRC4 are critical for its activation. Sirtuin3 (SIRT3) is the most thoroughly studied mitochondrial nicotinamide adenine dinucleotide (NAD + ) -dependent deacetylase. We wondered whether SIRT3 mediated-deacetylation could take part in NLRC4 inflammasome activation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 71 publications
0
28
0
Order By: Relevance
“…On the other hand, in primary peritoneal macrophages, Sirt3 deficiency had no significant effect on NLRP3 inflammasome activation. Interestingly, in this study, Sirt3 was shown to directly deacetylate another inflammasome component, NLR domain-containing protein 4 (NLRC4), to promote pyroptosis (Guan et al, 2021).…”
Section: Sirtuin 3 and Pyroptosismentioning
confidence: 70%
“…On the other hand, in primary peritoneal macrophages, Sirt3 deficiency had no significant effect on NLRP3 inflammasome activation. Interestingly, in this study, Sirt3 was shown to directly deacetylate another inflammasome component, NLR domain-containing protein 4 (NLRC4), to promote pyroptosis (Guan et al, 2021).…”
Section: Sirtuin 3 and Pyroptosismentioning
confidence: 70%
“…SIRT3 deficiency leads to significantly impaired NLRC4 inflammasome activation, ASC oligomerization, and pyroptosis both in vitro and in vivo . SIRT3 interacts with and deacetylates NLRC4 at Lys71 or Lys272 to promote its activation ( Guan et al, 2021 ). However, SIRT3 is dispensable for NLRP3 and AIM2 inflammasome.…”
Section: Other Less Known Post-translational Modificationsmentioning
confidence: 99%
“…Its expression is upregulated by TNF and the stress-mediated p53 activation [ 143 , 144 , 145 ]. NLRC4 contains a CARD domain, and therefore, can directly recruit pro-caspase 1 via CARD–CARD interaction to activate caspase 1, associates or co-localizes with ASC [ 143 , 146 ] for proteolytic cleavage of proinflammatory cytokines (pro–IL-1β and pro–IL-18) and GSDMD [ 147 , 148 ]. The pathogen recognition of NLRC4 is usually via a sensor NAIP (NLR family, apoptosis inhibitory proteins) [ 149 ].…”
Section: Nlrp3 and Nlrc4 Inflammasomesmentioning
confidence: 99%
“…In addition, leucine-rich repeat kinase 2 LRRK2 is an intrinsic regulator of NLRC4 and LRRK2 formed a complex with NLRC4 for its optimal phosphorylation at Ser533, which promotes inflammasome activation during S. typhimurium infection in macrophages [ 157 ]. Interestingly, just as a report showed, acetylation-induced NLRP3 activation can be reversed by SIRT2 [ 158 ]; also SIRT3 was found to promote NLRC4 inflammasome activation by deacetylation [ 148 ]. The involvement of NLRC4 in pathogen recognition was largely thought to be restricted to bacterial infections but recent studies revealed that dendritic cell NLRC4 regulates T cell response during influenza A virus infection.…”
Section: Nlrp3 and Nlrc4 Inflammasomesmentioning
confidence: 99%